Cultural capital of IT developers in Ukraine: exploratory case study - Diadko, Ievgeniia; Buko, Svitlana (Rozwój Regionalny i Polityka Regionalna, 2015)
Article focuses on the analysis of approaches to studying cultural capital of IT developers. Exploratory case study refers to the IT developers’ activity and focuses the cultural capital (CC) of the Ukrainian IT sector. Theoretical foundation of the study is based on the cultural capital theory referring to the value of social relations and networks. Research results demonstrate that Ukrainian IT developers accumulate CC through education: individual, in family, at school and with peers. Cultural capital could be transformed into other forms of capital: economic and social ones.